Przegląd wybranych metod rehabilitacji kończyny górnej u pacjentów po przebytym udarze niedokrwiennym mózgu = A review of selected methods for the rehabilitation of the upper extremity in patients after undergone brain ischemic stroke - Siminska, Joanna; Pietkun, Katarzyna; Głowacka, Iwona; Beuth, Wojciech; Nowacka, Krystyna; Hagner, Wojciech; Siedlecki, Zygmunt (Journal of Education, Health and Sport, 2016)
Siminska Joanna, Pietkun Katarzyna, Głowacka Iwona, Beuth Wojciech, Nowacka Krystyna, Hagner Wojciech, Siedlecki Zygmunt. Przegląd zaleceń postępowania fizjoterapeutycznego stosowanego w bólu kręgosłupa w odcinku lędźwiowym = Overview of recommendations physiotherapy used for spinal pain in the lumbar region. Journal of Education, Health and Sport. 2016;6(8):454-466. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60914 http://ojs.ukw.edu.pl/index.php/johs/article/view/3780 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 19.08.2016. PRZEGLĄD ZALECEŃ POSTĘPOWANIA FIZJOTERAPEUTYCZNEGO STOSOWANEGO W BÓLU KRĘGOSŁUPA W ODCINKU LĘDŹWIOWYM OVERVIEW OF RECOMMENDATIONS PHYSIOTHERAPY USED FOR SPINAL PAIN IN THE LUMBAR REGION Siminska Joanna1, Pietkun Katarzyna1,2, Głowacka Iwona1, Beuth Wojciech4,5, Nowacka Krystyna1,5, Hagner Wojciech1,5, Siedlecki Zygmunt3 1 Katedra i Klinika Rehabilitacji Collegium Medicum w Bydgoszczy 2 Katedra Kosmetologii i Dermatologii Estetycznej Collegium Medicum w Bydgoszczy 3 Klinika Neurochirurgii i Neurotraumatologii i Neurochirurgii Dziecięcej Collegium Medicum w Bydgoszczy 4 Wojewódzki Szpital Specjalistyczny we Włocławku 5 Kujawska Szkoła Wyższa we Włocławku Streszczenie Zespoły bólowe lędźwiowego odcinka kręgosłupa określane są również jako bóle kręgosłupa/ krzyża. Obecnie dolegliwości bólowe kręgosłup szczególnie w odcinku lędźwiowym stały się epidemią naszych czasów. Według A. Nowakowskiego określa się nimi dolegliwości, które zlokalizowane w okolicy lędźwiowej, lędźwiowo- krzyżowej i krzyżowo- biodrowej. Bóle krzyża jest to nazwa ogólna, gdyż występuje mnogość czynników, które powodują schorzenia odcinka lędźwiowego. Dolegliwość ta stwarza duże trudności diagnostyczne i jest obecnie ,,krzyżem dla lekarza” a co za tym idzie także fizjoterapeuty.[11] Charakter bólowy dolegliwości jest często trudny do określenia dla pacjenta. Charakterystycznie występują bóle począwszy od tępych, przeszywających, świdrujących, piekących, po takie, które wywołują odczucie lodowatego zimna. Lokalizacja objawów bólowych bywa różna. Chorzy zgłaszają bóle, które zlokalizowane są w całej okolicy lędźwiowo- krzyżowej lub tylko po jednej stronie kręgosłupa, bądź w okolicy stawów krzyżowo- biodrowych. Często promieniują wzdłuż jednej kończyny dolnej.[11] Większość ludzi, nie zdając sobie sprawy z przykrych konsekwencji, codziennie naraża swój kręgosłup na niebezpieczeństwo. Najczęściej schorzenia te są wynikiem braku dbałości o swój kręgosłup : złej postawy, nieodpowiedniego ułożenia podczas snu , braku umiejętności radzenia sobie ze stresem, złej diety. Nie można przecież jednak przestać dźwigać czy wykonywać czynności dnia codziennego, nie unikniemy też stresu. Słowa kluczowe: ból kręgosłupa, odcinek lędźwiowy kręgosłupa, rehabilitacja. Summary Pain syndromes of the lumbar spine are also referred to as back pain / cross. Currently, pain spine especially in the lumbar region have become epidemic of our time. According to A. Nowakowski defines them problems, which are located in the lumbar region, lumbar and sacral iliac cross flow. Low back pain is a generic name, because there is a multitude of factors that cause the disease of the lumbar. This condition creates great difficulties in the diagnosis and is now ,, cross for the doctor, "and thus also a physiotherapist. [11] The nature of pain symptoms is often difficult to determine the patient. Characteristically they are pain from the blunt, piercing, piercing, stinging, to those which produce the feeling of glacial cold. Location pain symptoms sometimes vary. Patients report pain, which are located throughout the area lumbar sacral or only on one side of the spine, or in the vicinity of the hip joint cross flow. Often radiate along one lower limb. [11] Most people unaware of the unpleasant consequences, every day puts your spine at risk. The most common diseases are the result of lack of attention to your spine: bad posture, improper alignment during sleep, lack of ability to cope with stress, poor diet. We can not, however, stop to carry or perform activities of daily life, not avoid or stress. Key words: pain in the spine, lumbar spine, rehabilitation.